Manajemen Pembelajaran Online Menggunakan Adobe Flash pada Mata Kuliah Pattiserie Terhadap Capaian Kompetensi - Angraini, Ezi; Giatman, M; Maksum, Hasan (AI Society & STMIK Indonesia, 2023)
Learning media is an instrument that greatly determines the success of the teaching and learning process. Because its existence can directly provide its own dynamics to students. After the spread of the Covid-19 outbreak had an effect on the world of education, changes to the learning system were directed to an online home study policy. This study aims to determine the effectiveness of Adobe Flash CS6 media in online learning towards competency achievement in the Pattiserie course. This research method uses a quantitative method by comparing student learning outcomes online during the pandemic with before the pandemic in the Pattiserie course at the IKK FPP UNP department. Based on data obtained from the 2017 and 2019 batch of Pattiserie semester scores, the average grade for the experimental class was 73.01 and the average grade for the control class was 88.53. From the results above, it can be concluded that a valid and practical media has not been able to replace the effectiveness of Pattiserie learning, in other words, this Pattiserie course is more competent if it is carried out practically in a laboratory because the hierarchy of practical courses must be carried out in a laboratory/workshop.